KEARIFAN LOKAL MASYARAKAT PADA PENGELOLAAN AGROFORESTRI DI DESA BATU NINDAN KABUPATEN KAPUAS - Cahyani Hanifah; Hafizianor Hafizianor; Asysyifa Asysyifa (Jurnal Sylva Scienteae, 2023)
Local wisdom is a form of behavior or mindset of the people of an area that is applied in the environment where they live. The purpose of this study was to examine the local wisdom of the community in managing agroforestry land in Batu Nindan Village. This research method is interviewing key respondent (such as village heads, community leaders, and agroforestry farmers) who have information related to the problem under study regarding forms of local community wisdom in managing agroforestry land. The interview method used is in-depth interviews to key respondent. The data were obtained from direct observations in the field. The results of the observation of this study are that there are three components, namely Ideological Superstructure (relating to the carrying out of a traditional ritual during land clearing called the ritual "Ala Ayuning or Dewase Ayu"), Social Structure (absence of customary institutions related to agroforestry land management) and Material Infrastructure (in processing the land is carried out with special treatments, such as making mounds, boiling and applying lime. This treatment is carried out because the condition of the land in Batu Nindan Village is including wetlands).Kearifan lokal adalah bentuk perilaku atau pola pikir dari masyarakat suatu daerah yang diterapkan di lingkungan tempat tinggalnya. Tujuan penelitian ini adalah mengkaji kearifan lokal masyarakat dalam pengelolaan lahan agroforestri di Desa Batu Nindan. Metode penelitian ini adalah wawancara kepada responden kunci (seperti Kepala Desa, Tokoh Masyarakat, dan Petani Agroforestri) yang mengetahui informasi terkait dengan masalah yang diteliti ini tentang bentuk kearifan lokal masyarakat dalam mengelola lahan agroforestri. Metode wawancara yang digunakan ialah wawancara secara mendalam (Indept Interview) kepada responden kunci. Data-data yang didapatkan dalam penelitian diperoleh dari hasil observasi secara langsung di lapangan. Hasil dari penelitian ini terbagi menjadi tiga komponen yaitu Supesrtruktur Ideologis (Struktur Sosial (tidak adanya kelembagaan secara adat yang berkaitan dengan pengelolaan lahan agroforestri) dan Infrastruktur Material (dalam pengolahan lahannya dilakukan dengan perlakuan khusus, seperti pembuatan guludan tanah, pendangiran dan pemberian kapur. Perlakuan tersebut dilakukan karena kondisi lahan di Desa Batu Nindan termasuk lahan basah).